أثر استراتيجية القطع المكسرة في تحصيل مادة اللغة العربية عند طلاب الصف الثاني المتوسط (Journal of the College of Basic Education, 2024)
The current research aims to identify (the effect of the broken pieces strategy on the achievement of the Arabic language subject for the students of the second intermediate grade).The researcher followed the experimental approach, as it is appropriate and suitable for the nature and purpose of her research, and the researcher identified the current research community as students of the second intermediate grade in the intermediate and secondary day schools for boys affiliated to the six general directorates in Baghdad Governorate for the academic year (2022-2023), and the researcher chose a sample for her research in a random way. Consisting of (64) students in Al-Ameen Intermediate School for Boys, affiliated to the Directorate of Education of Baghdad / Al-Rusafa II, and they were randomly distributed into two groups (experimental and control), with (32) for each group.The researcher studied the two groups of the same research, as it began on Sunday corresponding to 10/16/2022 and ended on Monday corresponding to 1/9/2023, with two sessions per week for each group, and the experiment continued for a full semester. The researcher prepared an achievement test consisting of (30) items distributed on Objective and essay questions applied to the experimental and control research groups at the end of the experiment, and the test was characterized by honesty, stability and objectivity, and the researcher processed the research data and its results by using the statistical bag (spss) by using the following equations: the t-test test for two independent samples, chi-square, difficulty coefficient, discrimination coefficient, effectiveness of alternatives, and Qodder's equation - Richardson 20, Cooper's equation and Cronbach's alpha equation. The research yielded the following results: The performance of the experimental group students outperformed the students of the control group